HUBUNGAN TINGKAT STRES, TIPE KEPRIBADIAN, DAN DUKUNGAN SOSIAL DENGAN MEKANISME KOPING PADA MAHASISWA TINGKAT SATU BOARDING SCHOOL FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR 2024 - Muhammad Fathurrohman Faisal; Irwan Syuhada; Wendy Handayani; Ronanarasafa, Ronanarasafa (Nusantara Hasana Journal, 2024)
A coping mechanism is a way used to deal with the stress or pressure faced. Coping strategies are different for each individual, one of which is carried out by students, especially medical students who are prone to experiencing stress. The factors that determine which coping mechanisms are most often used depend greatly on the level of stress experienced. The coping mechanisms used can also be influenced by a person's personality type. Apart from personality type, social support can also influence individual coping mechanisms. The aim of this research was to determine the relationship between stress levels, personality type, and social support with the coping mechanisms of First Level Boarding School Students, Faculty of Medicine, Al-Azhar Islamic University, Mataram. This type of research is observational analytic with a cross sectional approach. The population in this study was all first year boarding school students at the Faculty of Medicine, Al-Azhar Islamic University, Mataram, totaling 109 students. The sampling technique used purposive sampling with a total sample of 62 undergraduate boarding school students at Al-Azhar Islamic University, Mataram. The results of the analysis showed that 74.2% of students used adaptive coping mechanisms, 62.9% of students had moderate stress levels, 88.7% of students had introverted personality types, and 66.1% of students received high levels of social support. The results of the Chi Square test show that there is a relationship between coping mechanisms and stress level with a value of P = 0.002 (P < 0.005), there is also a relationship between coping mechanisms and personality type with a value of P = 0.044 (P < 0.005) and there is no relationship between coping mechanisms and social support with a value of P = 0.568 (P > 0.05).